Recurrent Acute Pancreatitis with Anomalous Pancreaticobiliary Ductal Union (Komi’s Type IIIc3) with Santorinocele in a Child: A Rare Case Report - Mishra, Vineet; Joseph, A. J.; Dutta, Amit Kumar; Chowdhury, Sudipto Dhar; Kurien, Reuben Thomas; Jaiswal, Saurabh; Patnaik, Itish; Kalra, Parika; Rajeeb, Sayd Mohamad (Journal of Digestive Endoscopy, 2017)
Anomalous pancreaticobiliary ductal union (APBDU) can cause recurrent acute pancreatitis. We describe the case of a 16-year-old boy with recurrent acute pancreatitis. The discussion provides a review of recent literature, supporting use of various diagnostic modalities and surgery as choice of treatment.
Keywords: Anomalous pancreaticobiliary ductal union; choledochal cyst; Komi classification; recurrent acute pancreatitis; santorinocele